(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
The objective of this study was to analyze the immediate influence of soft skills training on the level of engagement among organizational leaders in Argentina. To achieve this, an adapted version of the Utrecht Work Engagement Scale was used to assess leaders before and after participating in soft skills training programs. The results indicate a positive and significant relationship between the training and the increase in organizational engagement. Leaders showed a 2% improvement in their engagement. This finding suggests that investing in the development of soft skills, in addition to strengthening leadership, can be an effective strategy for increasing leader engagement. This is particularly relevant given the influence leaders have on generating engagement within their teams.